Change of Structural and Adsorption Properties Due to Isomorphous Substitution in Hydrotalcite-like Materials - Gamal M.S. El Shafei (Adsorption Science & Technology)
Samples of hydrotalcite-like compounds with the general formula [M 2+ 1-x M 3+ x (OH) 2 ] x+ •A x– •nH 2 O were prepared via coprecipitation through the addition of NaOH to mixed chloride salt solutions. On maintaining the M 2+ /M 3+ ratio equal to three, it was possible to effect isomorphous substitution. This led to the preparation of different compounds which could be compared to the parent material in which M 2+ = Ni and M 3+ = Al. Other divalent cations used were Mg 2+ and Zn 2+ with Cr 3+ and Fe 3+ being employed as trivalent cations. The ratio between cations of the same charge was unity in all the isomorphously substituted samples and substitution was conducted for one oxidation state only at a time. Hence, all samples contained a maximum of three different cations. The charge compensating anion in the interlayers, A, was identified as mainly CO 3 2– with the co-existence of Cl − anions to different extents. The structural and textural properties developed as a result of the substitutions effected were studied by XRD, IR, DTA, acid–base titration and mercury porosimetry measurements. Various samples were used for the adsorption of 4-chlorophenol to examine the effects on the adsorption properties arising from isomorphous substitution. The major effect having a marked influence on the adsorption properties arose from the nature of the compensating anion in the interlayers. Different tendencies of different cations to be accommodated in the layer structure resulted in different interlayer spaces and variable conformations of the charge compensating anion. In all cases, at low equilibrium concentrations, the adsorption of 4-chlorophenol (pH = 11) occurred at the edges of the layer structure accompanied by Cl − /OH − exchange. The increasing order in the amount of 4-chlorophenol adsorbed was matched by an increasing order in the interlayer space due to substitution. At higher values of the equilibrium concentration, the adsorption of both phenolate and OH − anions decreased. This was because such adsorption into the interlayer space to replace the CO 2– anion was diffusion-controlled, making the process improbable at high pH values.